Factor affecting user satisfaction in agricultural e-commerce applications: Facing the new normal - Alfa Nursyamiza Nusifera; Mukhamad Najib; Kirbrandoko Kirbrandoko (Journal of Innovation in Business and Economics, 2020)
Agricultural E-Commerce with a retail business model has a big challenge to become an alternative sales distribution of agricultural products. Consumer satisfaction and loyalty can be a strategy for companies to maintain and increase sales. The purpose of this study was to analyze the users of agricultural e-commerce application characteristics and variables that affect customer satisfaction and loyalty. It was conducted by a survey in the Greater Jakarta area, Indonesia. Research data were collected using a questionnaire with a convenience sampling method to 170 respondents. The majorities of respondents were women with an age range of 20-30 years. Structural Equation Modeling (SEM) results show that there is a significant influence between information quality, design, response, security, delivery on satisfaction, and satisfaction with loyalty. On the other hand, there is no significant difference between ability, payment, user service, and satisfaction. Companies can create loyalty programs to increase product purchase retention in agricultural e-commerce.